Non-Free Labor. Definition, Sectors, and Public Policies Around the World - Pinto Tortosa, Antonio Jesús (Palgrave MacMillan, 2022)
Non-free labor is unfortunately one of the biggest issues in the twenty-first century. Not only does it affect poor countries, but also it is possible to find examples in rich countries. One of the reasons for explaining this situation is that development and demand of different products in the global market makes it impossible for producers to meet the consumers’ requirements unless they cut down expenses in the production process. The working force is often the element in the production chain that suffers the cutting down of expenses the most, so that workers are paid less and less money, and in many cases no money at all, living in a near-to-slavery condition. The aim of this chapter is to define what non-free labor is, as well as to analyze the different economic sectors where we can find examples of non-free labor, describing in the end the main actions that governments undertake to stop such practices.
© The Author(s), under exclusive licence to Springer Nature Switzerland AG 2022
Keywords: Esclavitud - República Dominicana - S. XX- S. XXI; Esclavitud - Haití - S. XX- S. XXI; Haiti; Dominican Republic; Digital world; Neoliberalism; Non-free labour; Smuggling; Human trafficking; Agriculture; Textile industry; Sexual workers